مخطوط "مجموع ذكرت فيه ما عثرت عليه من تراجم بعض علماء قمار" للشيخ محمد الطاهر التليلي - بن عمر عبدالفتاح; دردور عبدالباسط; صوالح محمد نبيل; غرايسة عمار (University Of Eloued جامعة الوادي, 2023)
تهدف هذه الدراسة إلى التعريف بشخصية محمد الطاهر التليلي، وبمخطوطه الذي يحمل عنوان" مجموع ذكرت فيه ما عثرت عليه من تراجم بعض علماء قمار"، للوقوف على مضمونه ومنهجه الذي انتهجه، ومظهره الداخلي والخارجي، وعلى المصادر التي اعتمدها. ولقد توصلنا من خلال هذا البحث إلى جملة من النتائج ولعل من أبرزها أن ترجمة الشيخ محمد الطاهر التليلي للعلماء تميزت بالاختصار والتحري في العرض، والتجرد من العداء، وبالجمع بين الأسلوب العلمي والأدبي. This study aims to introduce the character of Muhammad Al-Tahir Al-Talili and his manuscript, entitled "A collection of what I found in the translation of some gambling scientists." This is to ascertain his content and methodology, his internal and external appearance, and the sources he adopted. Through this research, I have reached a number of conclusions. Perhaps the most prominent of these is that Sheik Mohammed Al-Taher's translation of scholars was characterized by brevity, investigation in presentation, devotion to hostility, and a combination of scientific and literary style.
دراسة وتحقيقا
Keywords: التليلي; عثرت; Al-Talili; A collection; I found; translation; gummar; study; investigation